Meta‐analysis and systematic review: Prevalence, graft failure, mortality, and post‐operative thrombosis in liver transplant recipients with pre‐operative portal vein thrombosis. Issue 2 (7th November 2021) - Yeo, Jun Wei; Law, Michelle Shi Ni; Lim, Joseph Chun Liang; Ng, Cheng Han; Tan, Darren Jun Hao; Tay, Phoebe Wen Lin; Syn, Nicholas; Tham, Hui Yu; Huang, Daniel Q.; Siddiqui, M. Shadab; Iyer, Shridhar; Muthiah, Mark
Abstract: Aims: This study seeks to evaluate the association between pre‐transplant portal vein thrombosis (PVT) and overall survival, graft failure, waitlist mortality, and post‐operative PVT after liver transplantation. Methods: A conventional pairwise meta‐analysis between patients with and without pre‐transplant PVT was conducted using hazard ratios or odds ratios where appropriate. Results: Prevalence of preoperative PVT was 11.6% (CI 9.70–13.7%). Pre‐operative PVT was associated with increased overall mortality (HR 1.45, 95% CI 1.27–1.65) and graft loss (HR 1.58, 95% CI 1.34–1.85). In particular, grade 3 (HR 1.59, 95% CI 1.00–2.51) and 4 (HR 2.24, 95% CI 1.45–3.45) PVT significantly increased mortality, but not grade 1 or 2 PVT. Patients with PVT receiving living donor (HR 1.54, 95% CI 1.24–1.91) and deceased donor (HR 1.52, 95% CI 1.21–1.92) liver transplantation had increased mortality, with no significant difference between transplant types ( P = .13). Furthermore, pre‐transplant PVT was associated with higher occurrence of post‐transplant PVT (OR 5.06, 95% CI 3.89–6.57). Waitlist mortality was not significantly increased in patients with pre‐transplant PVT. Conclusion: Graft failure, mortality, and post‐operative PVT are more common in pre‐transplant PVT patients, especially in grade 3 or 4 PVT. Prophylactic anticoagulation can be considered to reduce re‐thrombosis and improve survival.